Reklama w świetle legendy. „Dźwignia” Rafała Wojaczka - Pertek, Grzegorz (Poznańskie Studia Polonistyczne. Seria Literacka, 2014)
<span style="font-family: 'Times New Roman','serif'; font-size: 12pt; mso-fareast-font-family: 'ＭＳ 明朝'; mso-fareast-theme-font: minor-fareast; mso-fareast-language: PL; mso-ansi-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US">The article entitled “Rafał Wojaczek: Advertisement in the Light of a Legend” is the first part of a draft which tries to describe a breakthrough moment, in which the biography of Rafał Wojaczek coincides with the beginning of his literary output. The author makes a central point of the formula: “advertisement is the engine of trade” (appearing in the notebook collecting his early poetical notes from the period of studies at Polish philology), which is placed in contrast to the statement by Julian Przyboś: “the art of a poem is the engine of poetry”. The author, examining the earlier editions of Wojaczek’s poems explains (using the sociological and philosophical apparatus) the mechanisms conditioning the phenomenon of the reception of his poetry. At the same time, he launches the notion of pre-reception, which—being a labile notion, situated in the borderland between reception and advertise-ment—indicates a dual position of an object, to which the pre-reception refers (presence and absence at the same time). This, in turn, announces the poetic strategy of Wojaczek, embracing the form and the subject matter of a poem (expressiveness against a precise structure of a poem), and foretells a subsequent part focusing on the question of the actual reception, taking into consideration the somatic character of his output as well as its autothematic involvement.